Exploring Speaking Anxiety Levels Among EFL Students: Evidence from the English Language Education Study Program of Universitas Negeri Gorontalo - Frindi Meilani Hasan; Muziatun; Indri Wirahmi Bay (Universitas Islam Negeri Palopo, 2026)
Speaking anxiety remains one of the most common challenges experienced by English as a Foreign Language (EFL) learners, particularly in oral communication activities. This study aimed to identify the level of speaking anxiety among students of the English Language Education Study Programme at Universitas Negeri Gorontalo. The study employed a descriptive quantitative research design involving 110 students selected through purposive sampling from a population of 131 students who had completed speaking-related courses. Data were collected using the Foreign Language Speaking Anxiety Questionnaire (FLSAQ), an 18-item adaptation of the Foreign Language Classroom Anxiety Scale (FLCAS), and analyzed using descriptive statistics. The findings revealed that 45% of the participants experienced moderate speaking anxiety, 36% experienced high anxiety, and only 19% demonstrated low anxiety. The results indicate that speaking anxiety remains a prevalent issue among EFL students, with the majority of participants experiencing moderate to high levels of anxiety during English-speaking activities. Furthermore, the most significant sources of anxiety were speaking with native speakers, misunderstanding teacher correction, lack of self-confidence, and speaking without preparation. These findings suggest that speaking anxiety is influenced by both internal and external factors that may hinder students’ oral communication performance. The study highlights the importance of creating supportive classroom environments, providing constructive feedback, and implementing low-pressure speaking activities to help students develop confidence and reduce anxiety. The novelty of this study lies in its focus on pre-service English teachers in an Indonesian higher education context, contributing to the growing body of research on foreign language speaking anxiety.